Cellular Imaging of Visual Cortex Reveals the Spatial and Functional Organization of Spontaneous Activity - Ch'Ng, Yeang H.; Reid, Clay (Frontiers in Integrative Neuroscience, 2010)
The cerebral cortex is never silent; even in primary sensory areas there is ongoing neural activity in the absence of sensory input. Correlations in spontaneous activity can provide clues about network structure, but it has been difficult to record from enough nearby neurons to sample these correlations well. We used in vivo two-photon calcium imaging to demonstrate sparse patterns of correlated spontaneous activity among groups of 150 simultaneously imaged cells. In cat visual cortex, correlations fell off sharply with distance, by 50% within 240 micrometers, but in the rat there was little dependence on spatial separation up to 400 micrometers. In both species, cells that responded best to visual contours of a specific orientation were spontaneously co-active, suggesting that functionally related cells are organized into distinct subnetworks. Although these subnetworks are clustered in the cat, they are intermingled in the rodent, arguing for specific connections within the local cortical network.